(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
It has been collect ten Leuciscus vorax Heckel, 1848 fishes in the period from 15/6 to 15/9, of the year 2020 C. from the Al-mashrooa river which connected to the Euphrates River at Al-Musaib region, and after dissection and examine the samples it have been isolate the crustacean parasite Lamproglena chinensis and the Excysts Metacercaria Centrocestus formosanus Phase from the gill and it’s isolation for the first time from this fish, then it regarded as a new hosts to the parasites above in Iraq.